Systematic Review - Combining Neuroprotection With Reperfusion in Acute Ischemic Stroke - Vos, E. M.; Geraedts, V. J.; van der Lugt, A.; Dippel, D. W. J.; Wermer, M. J. H.; Hofmeijer, J.; van Es, A. C. G. M.; Roos, Y. B. W. E. M.; Peeters-Scholte, C. M. P. C. D.; van den Wijngaard, I. R. (Frontiers in Neurology, 2022)
Background Clinical trials of neuroprotection in acute ischemic stroke (AIS) have provided disappointing results. Reperfusion may be a necessary condition for positive effects of neuroprotective treatments. This systematic review provides an overview of efficacy of neuroprotective agents in combination with reperfusion therapy in AIS. Methods We performed a systematic review of the literature based on electronic databases (PubMed, Embase, Web of Science, Cochrane Library, Emcare). All randomized controlled trials in which patients were treated with neuroprotective strategies within 12 hours of stroke onset in combination with intravenous thrombolysis (IVT), endovascular therapy (EVT), or both were included. Results We screened 1764 titles/abstracts and included 30 full reports of unique studies with a total of 16160 patients. In 15 studies neuroprotectants were tested for clinical efficacy, where all patients had to receive reperfusion therapies, either IVT and/or EVT. Heterogeneity in reported outcome measures was observed. Treatment was associated with improved clinical outcome for: 1) uric acid in patients treated with EVT and IVT, 2) nerinetide in patients who underwent EVT without IVT, 3) imatinib in stroke patients treated with IVT with or without EVT, 4) remote ischemic perconditioning and IVT, and 5) high-flow normobaric oxygen treatment after EVT, with or without IVT. Conclusion Studies specifically testing effects of neuroprotective agents in addition to IVT and/or EVT are scarce. Future neuroprotection studies should report standardized functional outcome measures and combine neuroprotective agents with reperfusion therapies in AIS or aim to include prespecified subgroup analyses for treatment with IVT and/or EVT.